2006
DOI: 10.1037/1064-1297.14.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in physical dependence on orally self-administered phencyclidine (PCP) in rhesus monkeys (Macaca mulatta).

Abstract: Withdrawal from orally self-administered phencyclidine (PCP) has been shown to alter operant baselines of food-maintained responding. The goal of the present study was to determine whether there are sex differences in these alterations. Seven female and 7 male rhesus monkeys (Macaca mulatta) were given concurrent access to PCP and water under fixed ratio (FR) 8 schedules during 2 daily sessions that alternated with 2 sessions during which pellet deliveries were contingent on lever presses under an FR 64 schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
16
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 37 publications
13
16
0
Order By: Relevance
“…These results were consistent with those of Perry et al (2006) who found that PCP withdrawal disrupted foodmaintained performance (FR 64) to a greater extent in males than females. In the present study, the MAD values for SACC during PCP FR access were not different than during BL-W; thus, PCP intake did not alter impulsivity for SACC, while PCP withdrawal clearly increased it.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results were consistent with those of Perry et al (2006) who found that PCP withdrawal disrupted foodmaintained performance (FR 64) to a greater extent in males than females. In the present study, the MAD values for SACC during PCP FR access were not different than during BL-W; thus, PCP intake did not alter impulsivity for SACC, while PCP withdrawal clearly increased it.…”
Section: Discussionsupporting
confidence: 92%
“…Recent work measuring changes in food-maintained responding during PCP withdrawal indicated that male monkeys showed a more severe and longer duration of behavioral withdrawal effects than females when PCP access was terminated (Perry et al 2006). These results were consistent with studies in rats injected with pentobarbital, ETOH (Devaud and Chadda 2001), morphine (Cicero et al 2002;e.g., Suzuki et al 1985), and methaqualone (Suzuki et al 1988).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, HiS rats outperform LoS rats under many of the same drug-related conditions, such as acquisition , escalation (Perry et al, 2006a), and reinstatement (Perry et al, 2006a) of drug-seeking behavior. Interestingly, one area where males show a greater drug effect than females is in disruptions in operant behavior during drug withdrawal (Perry et al, 2006b), and recent evidence suggests that LoS rats also exceed HiS rats in their behavioral suppression during drug withdrawal (Dess et al, 2005). The literature and the present results emphasize the salience of selective breeding for saccharin intake and sex as factors that influence vulnerability to drug abuse.…”
Section: Delay Discounting For Cocainesupporting
confidence: 61%
“…Sex differences have been demonstrated in behavioral dependence upon on orally self-administered PCP. Perry et al (2006) found that males exhibit a stronger and more prolonged disruption in food-maintained behavior after withdrawal from PCP than females.…”
Section: Introductionmentioning
confidence: 96%